Carcharhinus limbatus - Carneiro, Miguel; Martins, Rogélia; Landi, Monica; Costa, Filipe O. (Zenodo, 2014)
□ Carcharhinus limbatus (Müller & Henle, 1836) – Blacktip shark; Tubarão-de-pontas-negras ① , ② , Tubarão or Anequim ③ Arruda (1997) considered a doubtful presence of C. limbatus off the Azores. Quéro et al. (2003) indicated the presence of the species in Portugal, without mentioning the geographical area of occurrence. Ebert & Stehmann (2013) indicated the presence of the species to southern mainland Portugal, based on its geographical distribution. : Published as part of Carneiro, Miguel, Martins, Rogélia, Landi, Monica & Costa, Filipe O., 2014, Updated checklist of marine fishes (Chordata: Craniata) from Portugal and the proposed extension of the Portuguese continental shelf, pp. 1-73 in European Journal of Taxonomy 73 on page 12, DOI: 10.5852/ejt.2014.73, http://zenodo.org/record/3866515 : {"references": ["Arruda L. M. 1997. Checklist of the marine fishes of the Azores. Arquivos do Museu Bocage, Nova Serie 3 (2): 3 - 164.", "Quero J. - C., Porche P. & Vayne J. - J. 2003. Guide des Poissons de l'Atlantique Europeen. Delachaux et Niestle, Paris.", "Ebert D. A. & Stehmann M. F. W. 2013. Sharks, batoids, and chimaeras of the North Atlantic. FAO Species Catalogue for Fishery Purposes no. 7, Food and Agriculture Organization, Rome."]}